2004
DOI: 10.1598/rrq.39.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Postsecondary education and some dimensions of literacy development: An exploration of longitudinal evidence

Abstract: S This exploratory study analyzed longitudinal data from 18 institutions to track the literacy development of 1,054 students during the first three years of college. Reading comprehension and attitude toward literacy activities were assessed at the beginning and end of the study. Students responded annually to questionnaires about college experiences and provided background data. Linear regression procedures were used to predict growth on the outcome measures. With potential confounding influences on literacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 50 publications
0
27
1
Order By: Relevance
“…The positive attitude toward literacy scale (Bray et al 2004;Pascarella et al 2007) includes five items, each with identical five Likert-scale response options, that ask the respondent to specify their degree of interest in reading for enjoyment and writing as a means of examining or processing one's thoughts or emotions. Literature often provides access to varying values, perspectives, and attitudes about society.…”
Section: Discussionmentioning
confidence: 99%
“…The positive attitude toward literacy scale (Bray et al 2004;Pascarella et al 2007) includes five items, each with identical five Likert-scale response options, that ask the respondent to specify their degree of interest in reading for enjoyment and writing as a means of examining or processing one's thoughts or emotions. Literature often provides access to varying values, perspectives, and attitudes about society.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that literacy, operationalized as performance on a range of comprehension tests, operates as both a selection factor and an outcome in higher education (Bray et al, 2004;Reder, 2000), but that many postsecondary students (22%) do not meet general comprehension benchmarks for adult literacy (Reder, 2000). Less is known about the role of wordlevel processes in postsecondary achievement.…”
Section: Reading and Postsecondary Academic Achievementmentioning
confidence: 99%
“…Despite the popularity of the college sophomore as a research participant, large-scale studies of college students' literacy typically have included measures of text comprehension only, not component reading skills (e.g., Bray, Pascarella, & Pierson, 2004;Reder, 2000; but see Cunningham, Stanovich, & Wilson, 1990;Perfetti & Hart, 1999 for exceptions). Those investigators who have examined postsecondary students' component reading skills have studied relatively small samples, often contrasting groups selected for particular ability levels (e.g., Bell & Perfetti, 1994;Bruck, 1998;Haenggi & Perfetti, 1994;Jackson & Doellinger, 2002, Martino & Hoffman, 2002Sabatini, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The final dependent variable-end of fourth-year PATL-is a measure of the extent to which an individual personally enjoys literacy activities, such as reading literature, poetry, scientific texts, and/or historical material, and expressing his or her ideas through writing (Bray, Pascarella, & Pierson, 2004). The PATL scale is positively correlated with reading unassigned books, reading comprehension, and library use within college student samples.…”
Section: Variablesmentioning
confidence: 99%
“…The PATL scale is positively correlated with reading unassigned books, reading comprehension, and library use within college student samples. The reliability of the PATL scale ranges from .70 to .72 in samples of college students (Bray et al, 2004;Loes, Salisbury, & Pascarella, 2013). …”
Section: Variablesmentioning
confidence: 99%